Influence of Individual Phospholipids on the Physical Properties of Oil‐Based Suspensions. (23rd October 2013) - Arnold, G.; Schade, E.; Schneider, Y.; Friedrichs, J.; Babick, F.; Werner, C.; Rohm, H.
Abstract: The impact of soybean lecithin and three individual phospholipids at different concentration ( C PL ) on rheology and sedimentation behavior of sugar/soybean oil suspensions ( ϕ = 0.31) was studied and compared with attraction and retraction forces between sugar surfaces in soybean oil as measured by atomic force microscopy (AFM). In general, a surfactant‐induced reduction of yield stress, apparent viscosity and sediment volume of the suspensions coincides with a decrease of adhesive interactions between sugar particles in soybean oil. Although the general influence of individual phospholipids and soybean lecithin is comparable, it is concluded from investigations at low C PL that individual phospholipids exhibit a less pronounced impact on the analyzed parameters. Furthermore, at low C PL, binary mixtures of the phospholipids are more efficient than individual phospholipids as regards the reduction of yield stress and sediment volume. While the same tendency was detectable for AFM results, these differences were not statistically verified. Slight differences were also evident when comparing individual phospholipids and their influence on rheology and sedimentation which are, however, not in line with the results of AFM. A general understanding of these interrelations between surfactant composition and possible synergistic or antagonistic effects in mixtures of individual phospholipids contributes to optimizing lecithin composition with respect to functionality.